CORONAVIRUS and challenges for dental care (Research, Society and Development, 2021)
In Brazil, the first case of COVID-19 appeared on February 26, 2020. The government, together with the Ministry of Health and the World Health Organization, created measures to contain the epidemic. Thus, the objective is to report the experience of the Institute for the Promotion and Assistance to Health of Servants of the State of Sergipe (IPESAÚDE) in the provision of dental care during the pandemic period by COVID-19 between April and July 2020, to draw a comparison between the number of services and specialties sought in the same period in 2019, as well as presenting the protocols instituted for the performance of dental care at the time of the pandemic. Methodology: Descriptive cross-sectional research, which will report the dental care and biosafety protocol adopted by IPESAÚDE during the pandemic as compared to the previous period. Results: In the months of April to July 2020, 2110 patients were treated, with permanent restorations being the most prevalent procedures. In the same period of 2019, 10557 patients were treated. When comparing the productions, there is a statistically significant difference (Kruskall Wallis - followed by Student Newman Keuls) between the months of 2020 and 2019. In 2020 there was a reduction of 80.3% in general services when compared to the same period in 2019. At the same time, there was a reduction of 80.1% in the demand for emergency care. There have been changes in screening and care procedures, and biosafety protocols have been put in place. Conclusion: There was an initial reduction in the number of visits, with a significant increase in July 2020. Biosafety protocols were implemented.